2012
DOI: 10.1093/humrep/des362
|View full text |Cite
|
Sign up to set email alerts
|

Microarray analysis reveals abnormal chromosomal complements in over 70% of 14 normally developing human embryos

Abstract: This research was supported by the Instituut voor de aanmoediging van innovatie door Wetenschap en Technologie in Vlaanderen (IWT-Vlaanderen). A.M. is a PhD student at the IWT-Vlaanderen. C.S. is a postdoctoral fellow at the FWO Vlaanderen. There are no competing interests.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
116
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 179 publications
(121 citation statements)
references
References 33 publications
4
116
1
Order By: Relevance
“…Where studied, most pregnancy losses are related to aneuploidy or other severe genetic conditions that are incompatible with extrauterine life (Boue et al 1975a,b;De Braekeleer and Dao 1990). For example, apparently healthy 2-d-old embryos have .70% aneuploidy (Mertzanidou et al 2013) and congenital heart disease is identified in 10% of stillbirths (Hoffman 1995 In 2011, there were 3,952,841 births in the United States Martin et al 2013). Approximately 10% of all newborns born in the United States are admitted to a NICU secondary to either a birth defect, prematurity or a complication of delivery (Schwartz et al 2000;Bettegowda et al 2010).…”
Section: Impact and Incidence Of Monogenic Diseasesmentioning
confidence: 99%
“…Where studied, most pregnancy losses are related to aneuploidy or other severe genetic conditions that are incompatible with extrauterine life (Boue et al 1975a,b;De Braekeleer and Dao 1990). For example, apparently healthy 2-d-old embryos have .70% aneuploidy (Mertzanidou et al 2013) and congenital heart disease is identified in 10% of stillbirths (Hoffman 1995 In 2011, there were 3,952,841 births in the United States Martin et al 2013). Approximately 10% of all newborns born in the United States are admitted to a NICU secondary to either a birth defect, prematurity or a complication of delivery (Schwartz et al 2000;Bettegowda et al 2010).…”
Section: Impact and Incidence Of Monogenic Diseasesmentioning
confidence: 99%
“…It has been previously shown that almost 50% of the embryos created by ARTs are mosaic, containing both normal (diploid) and abnormal (non-diploid) cells. [12][13][14][15] With respect to FP results, the contribution of mosaicism to the FP rate (FP ¼ 19.1%) in the overall data, reaches 54%. FP diagnosis is characterized as more benign as it does not lead to the initiation of an affected pregnancy, although it may decrease the number of genetically transferable embryos, hence reducing the probability of achieving a pregnancy.…”
Section: Discussionmentioning
confidence: 91%
“…During the first mitotic divisions in human preimplantation development, improper segregation of chromosomes might occur, causing high rates of aneuploidy and mosaicism [11]. Several studies showed that a majority of preimplantation embryos are diploid-aneuploid mosaic [12][13][14]. Chow et al [14] applied array comparative genomic hybridization to analyze high percentage of blastomeres from good quality day 3 embryos of young patients (with no known indication for PGD).…”
Section: Resultsmentioning
confidence: 99%
“…These embryos showed a high degree of mosaicism and less than 20 % euploidy. It is likely that mosaic embryos with a low number of abnormal blastomeres have self-correction mechanisms that enable normal implantation [13,14]. It has been shown that abnormal cells can be forced away from the embryonic inner cell mass leading to a viable euploid embryo [11].…”
Section: Resultsmentioning
confidence: 99%